Measuring the vocabulary burden of popular English songs - Rick Romanko (Vocabulary Learning and Instruction)
This study measured the vocabulary burden of popular English songs to determine what vocabulary is needed to understand 95% and 98% of the words in songs. The researcher analyzed the vocabulary in 2,175 songs, which consisted of 678,309 tokens. The results showed that knowledge of the most frequent 2,000 word families and proper nouns and marginal words provided 96.05% coverage, and knowledge of the most frequent 5,000 word families and proper nouns and marginal words provided 98% coverage of the English used in songs in the corpus.